Infertility‐related knowledge in childbearing‐age women with breast cancer after chemotherapy. Issue 5 (16th July 2019) - Huang, Sheng‐Miauh; Tseng, Ling‐Ming; Lai, Jerry Cheng‐Yen; Lien, Pei‐Ju; Chen, Ping‐Ho
Abstract: Aim: The purposes of this study were to describe the degree of knowledge and explore the factors associated with knowledge of infertility among women of childbearing age with breast cancer. Methods: In this cross‐sectional study, we recruited women of childbearing age with a diagnosis of breast cancer who had completed chemotherapy at a hospital in Taipei from 2015 through 2016. Face‐to‐face interviews were completed with 201 (62%) of 324 eligible women, asking about sociodemographic variables, disease and treatment characteristics, fertility intention, and infertility‐related knowledge. Results: The result showed one in 10 women had thought about becoming pregnant after completion of breast cancer chemotherapy. The mean score of infertility knowledge among participants was low, especially for general knowledge. Women with higher levels of education had better knowledge scores. Fertility intention score, especially for the domain of the pregnant risk, was negatively associated with infertility knowledge score. Conclusion: Women with breast cancer lacked knowledge about infertility and underestimated the possibility of infertility. We suggest future patient education on infertility after cancer treatment and about reproductive technology in oncologic practice before treatment begins. SUMMARY STATEMENT: What is known about this topic? Women with cancer diagnosed during the reproductive age are interested in a subsequent pregnancy. Less than half of childbearing‐age women with cancer have a comprehensive discussion about the potential impact of cancer therapy on fertility with the oncology physician. Reproductive‐age women with breast cancer have gaps in their knowledge of fertility planning as breast cancer survivors. What this paper adds? One in 10 women had thought about becoming pregnant after completion of breast cancer chemotherapy. Most women with breast cancer lack sufficient general and cancer‐specific knowledge about infertility. Factors associated with knowledge of infertility are fertility intention and education level. The implications of this paper: Results offer oncological nurses an understanding of fertility needs and infertility‐related knowledge in childbearing‐age women with breast cancer. Clinical nurses should continue to assess fertility willingness and knowledge of infertility in women with cancer both before and after cancer treatments. Comprehensive education about fertility and infertility in Taiwan is suggested.